Patient-centred outcomes for prehospital trauma trials: A systematic review and patient involvement exercise. (October 2019) - Hancox, James M; Toman, Emma; Brace-McDonnell, Samantha J; Naumann, David N
Introduction: Outcome measures are used in clinical trials to determine efficacy of interventions. We aimed to determine which outcome measures in prehospital major trauma trials have been reported in the literature, and which of these are most patient-centred. Methods: A systematic review identified outcomes reported in prehospital clinical trials of major trauma patients. A search was undertaken using Medline, Embase, clinicaltrials.gov, Web of Science and Google Scholar. Data were summarised by dividing outcomes into common themes which were presented to a Patient and Public Involvement group consisting of trauma survivors and their relatives. This group ranked the categories of outcomes in order of most importance, and agreed consensus statements regarding these outcome measures. Results: There were 27 eligible studies, including 9, 537 patients. Outcome measures were divided into nine categories: quality of life; length of stay; mortality/survival; physiological parameters; fluid/blood product requirements; complications; health economics; safety and feasibility; and intervention success. Of these, mortality/survival was the most commonly reported category, but over multiple timescales. The Patient and Public Involvement group agreed that the most important category was quality of life, and that mortality/survival should only be reported if concurrently reported with longer term quality of life. Length of stay and health economics were not considered important. Conclusions: Outcome measures in prehospital clinical trials in major trauma have been heterogeneous, inconsistent, and not necessarily patient-centred. Trauma survivors considered quality of life and mortality most important when combined. Consensus is required for consistent, patient-centred, outcome measures in order to investigate interventions of meaningful impact to patients.